DARI MUSHAF KE LAYAR: DAMPAK POSITIF TEKNOLOGI PADA STUDI AL-QUR’AN ONLINE - Jamiatul husna; Abdur Razzaq; Kristina Imron (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In the increasingly advanced digital era, information and communication technology has significantly transformed the way Muslims access and study the Quran. This study aims to analyze the positive impact of technology on online Quran study by highlighting aspects of accessibility, interactivity, religious digital literacy, and the formation of a global Muslim community. The approach used was qualitative library research, through a literature review of scientific journals, official agency reports, and online sources related to digital Quran learning.The research gap underlying this study is that most previous studies have focused solely on the technical and pedagogical aspects of technology-based learning without examining its impact on spiritual understanding, religious digital literacy, and scholarly authority in the context of online Quran learning. Furthermore, there are limited studies that integrate multimedia learning theory with Islamic spiritual values ​​and explore the formation of a global Muslim community in the digital space.The results show that digital technology expands access to the Quran through smartphones, applications, and online platforms that support interactive and multimedia learning. These innovations enrich understanding of the sacred text and strengthen connectivity among Muslims worldwide. However, challenges arise in terms of source validity, interpretive authority, and user digital literacy. This research emphasizes the importance of using technology wisely and spiritually to develop a generation of Muslims who are intelligent, moral, and have a global perspective.